Hubungan keterjangkauan dan kualitas layanan BPJS kesehatan terhadap kepuasan layanan puskesmas pada masyarakat berpenghasilan rendah di wilayah 3T - Kiki Andrean; Dwi Noerjoedianto; Arnild Augina Mekarisce; Andy Amir (Holistik Jurnal Kesehatan, 2026)
Background: Limited access to and quality of social security administering agency services in underdeveloped, frontier, and outermost (3T) regions is a major challenge for low-income communities and has the potential to reduce patient satisfaction at community health centers. Geographical barriers, limited facilities, and a lack of health resources often impact the effectiveness of health services in remote areas. Purpose: To analyze the relationship between service accessibility and service quality, as well as patient satisfaction among participants of the social security administering agency in low-income communities in 3T regions. Method: This study used a quantitative observational design with a cross-sectional approach. A total of 106 respondents were selected using a multistage and purposive sampling technique. This study was conducted at the Muara Kibul Community Health Center and the Aur Berduri Community Health Center in Merangin Regency since February 2025. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data were analyzed using univariate and bivariate analyses, using the chi-square test to determine the relationship between variables. Results: Most respondents rated service affordability as good, particularly in economic, language, and social aspects, although geographic barriers remain a challenge. Service quality was rated as quite good in terms of reliability, but responsiveness, assurance, empathy, and tangibles still need improvement. Statistical analysis showed a significant relationship between service affordability and patient satisfaction (p = 0.000), as well as between service quality and patient satisfaction (p = 0.000). Respondents with poor service affordability and quality were at higher risk of experiencing dissatisfaction with healthcare services. Conclusion: Service affordability and quality are important factors influencing patient satisfaction among participants of the social security administration for health in the 3T regions. Improvements in health infrastructure, transportation access, responsiveness of healthcare workers, and supporting facilities are crucial to increasing patient satisfaction and strengthening healthcare services in remote areas. Suggestion: Further research is recommended to use a larger sample size and cover more health centers in the 3T region, so that the research results are more representative.   Keywords: Low-Income Communities; Patient Satisfaction; Service Affordability; Service Quality; Social Security Administration for Health.